Analysis of Pesticide Residues in Chili Local (Capsicum annum) in The Region of Mandailing Natal Regency (Jurnal Online Pertanian Tropik, 2020)
Abstract Pesticides are chemicals always applied to various types of plant coomodities. The most widely applied pesticide applications are horticultural crops. The purpose of this study was to determine the organophosphate pesticide residues contained in local chili in Mandailing Natal regency. The research method in the form of a survey conducted on several local chili farmers and traders in the Mandailing Natal area.In this study, 2 main locations of chili cultivation were taken namely in the village of Sibanggor Julu and Tangga bosi. The study was interviewing 5 local chili farmers. The results showed that the local chili which was observes in the two villages contained pesticide residues. Pesticide residues found in the village og Sibanggor Julu exceed the maximum residue limit (BMR), namely Dimethoad 127,7504 mg/kg and chlorpyrifos 0,1513 mg.kg. As for the Tangga bosi  profenofost 7,4302 mg/kg and dimethoad 30,0019 mg/kg.